Networking and computing: from the chip to the web - Kropf, Peter; Plaice, John (My University, 1996)
There are two fundamental trends in the development of computers: the miniaturization of components and the increase in communication capacities. The combination of these two trends is leading to a qualitatively new situation, in which the same techniques will be appli- cable at all scales of computing, be they at the chip level or at the level of the World Wide Web (WWW).
, 1996